STUDY OF TIDAL CURRENT ELLIPSE IN THE INDONESIAN THROUGHFLOW EXIT - Beliyana, Erlin
Indonesian seas are strongly affected by strong semidiurnal tidal signals (M2 and S2) from the Indian Ocean and diurnal signals (K1 and O1) from the Pacific Ocean. Therefore, within the internal seas, there is possibility of mixed tides (semidiurnal and diurnal signals). This research is focused on determining tidal current ellipses and Fast Fourier Transform of residual currents and also connection between these two parameters based on the velocity data measured during the INSTANT (International Nusantara Stratification and Transport) program. The velocity data from Lombok and Ombai Straits and Timor passage from 2004 to 2006 are analyzed. Characteristics of tidal current data at certain fixed depths are processed and calculated using MATLAB software and present the variability of residual and tidal current in the Indonesian Throughflow (ITF) exit. In Lombok and Ombai Strait currents tend to move meridionally (north – south) and show semidiurnal tidal signals more dominant than diurnal tidal signals. Meanwhile, in Timor Passage dominated by both semidiurnal and diurnal signals. Diurnal components K1 and O1 and semidiurnal components M2 and S2 have different rotation of current vectors and different direction of initial motion. The semidiurnal M2 component is most dominant tidal signal in the six study areas meanwhile residual signals dominated by fortnightly, intraseasonal, and semiannual signals in the three major ITF exit. We can conclude that tidal current has no effect on ITF meanwhile ITF has effect on tidal current ellipse indirectly. ITF which varies seasonally then it will effect on generation and propagation on internal tides seasonally. This internal tides which varies seasonally has effect on different rotation of tidal current ellipse in western and eastern season.